RAIM DALAM RANGKA MENDUKUNG IMPLEMENTASI SISTEM NAVIGASI PENERBANGAN BERBASISKAN SATELIT DI INDONESIA (RAIM IN THE IMPLEMENTATION OF SATELLITE BASED NAVIGATION IN INDONESIAN AIR TRAFFIC MANAGEMENT) - Septiawan, Reza Septiawan; Sutedjo, Bayu; Sarotama , Afrias (Indonesian Journal of Aerospace, 2012)
Receiver Autonomous Integrity Monitoring (RAIM) is a method to monitor the integrity of GPS using mesurement to redundant satellites on the receiver side. Comonly 2 algorithm are used to perform RAIM, i.e. snapshot method and sequential method. In snapshot method, single set measurement of GPS signal is used, meanwhile in sequential method several sets of measurements (past and current) GPS signal are used. Therefore, the sequential method has the capacity to detect position failure due to low fault to noise ratio. The low fault to noise ratio is mostly caused by the satellite’s position at the time of position measurement. RAIM is very useful for GPS users to be able to determine the whether the GPS can give accurate position, based on its satellite’s positions, satellite’s service life or error in the receivers. Such accuracy is important especially for the use in GPS navigation sistem in Air Traffic Management (ATM). The disturbance can also be caused by ionosfer condition. In order to support the use of GPS navigation system in ATM in Indonesia, Communication Navigation Surveillance-ATM (GPS CNS-ATM) team of BPPT perform simply RAIM asessment that can be informed to the flightcrew or Air Traffic Center, to be informed via Notice To Air Men (NOTAM). The GPS signal observation is done in 5 different locations in Indonesia.